Development of Creative Economy Based on Culinary Tourism in Pasar Lama Tangerang to Enhance Competitiveness and Sustainability - Wibowo, Fransiscus Xaverius Pudjo; Chandra, Yopie; Widiyanto, Gregorius (International Journal of Business and Information Technology, 2025)
This research seeks to explore the Culinary Tourism Organization in Tangerang through the lens of Smart Branding, using the Old Market Culinary Area as a specific example. A descriptive qualitative approach is utilized for this study, collecting information via methods such as observation, interviews, and document analysis. City Branding, which can be interpreted as a city emblem in Indonesian, is an element of Smart Branding that underpins the effectiveness of Smart Cities in the tourism industry. This suggests that well-structured tourist destinations will be even more attractive, especially since culinary tourism is not the same as conventional tourism. Culinary tourism prioritizes the quality of food, satisfaction with taste, and the originality of the dishes offered. The researcher points out that there is a pressing need to address certain public amenities that fall short, like restrooms, as well as the absence of clear distinctions between halal and non-halal cuisine. These factors are seen as crucial for improving visitor comfort and adding to the visual appeal of the culinary area. Culinary tourism refers to a travel experience that draws people in by offering them the opportunity to taste and cook different regional foods from the places they visit.